2015
DOI: 10.1128/iai.00322-15
|View full text |Cite
|
Sign up to set email alerts
|

In Contrast to Chlamydia trachomatis, Waddlia chondrophila Grows in Human Cells without Inhibiting Apoptosis, Fragmenting the Golgi Apparatus, or Diverting Post-Golgi Sphingomyelin Transport

Abstract: bThe Chlamydiales are an order of obligate intracellular bacteria sharing a developmental cycle inside a cytosolic vacuole, with very diverse natural hosts, from amoebae to mammals. The clinically most important species is Chlamydia trachomatis. Many uncertainties remain as to how Chlamydia organizes its intracellular development and replication. The discovery of new Chlamydiales species from other families permits the comparative analysis of cell-biological events and may indicate events that are common to al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…This contrasts with C. abortus infection which results in necrotising placentitis and vasculitis present throughout the full thickness of the inter-cotyledonary areas and deep within the cotyledon tissue also. It has been suggested from the observed differences in the intracellular inclusion formation, substrate sequestration and the absence of anti-apoptotic activity of W. chondrophila compared to C. trachomatis that the organism may be perhaps more akin to a facultative rather than obligate pathogen in mammalian cells, in contrast with other classical chlamydial species15. These differences have been suggested to reflect a reduced level of pathogenicity, and explain the sporadic identification of W. chondrophila associated with clinical disease.…”
Section: Discussionmentioning
confidence: 98%
“…This contrasts with C. abortus infection which results in necrotising placentitis and vasculitis present throughout the full thickness of the inter-cotyledonary areas and deep within the cotyledon tissue also. It has been suggested from the observed differences in the intracellular inclusion formation, substrate sequestration and the absence of anti-apoptotic activity of W. chondrophila compared to C. trachomatis that the organism may be perhaps more akin to a facultative rather than obligate pathogen in mammalian cells, in contrast with other classical chlamydial species15. These differences have been suggested to reflect a reduced level of pathogenicity, and explain the sporadic identification of W. chondrophila associated with clinical disease.…”
Section: Discussionmentioning
confidence: 98%
“…This mitochondrial recruitment helps Waddlia to get access to large amounts of lipids and ATP, that are the required energy sources likely needed for its extended metabolic capacities and for its fast replication in a large variety of cell lines. This fast replication likely explains that W. chondrophila exhibits a faster cytotoxicity compared to C. trachomatis in HeLa human cervical epithelial cell [37]. However, some features of C. trachomatis infection, such as the arrangement of cytoskeletal structures around the inclusions, degradation of host cell proteins by proteolytic activity, inhibition of apoptosis, fragmentation of the Golgi apparatus and sphingomyelin transport to inclusion, were not observed during W. chondrophila infection [36,37].…”
Section: Mode Of Transmission Comments Referencesmentioning
confidence: 74%
“…This fast replication likely explains that W. chondrophila exhibits a faster cytotoxicity compared to C. trachomatis in HeLa human cervical epithelial cell [37]. However, some features of C. trachomatis infection, such as the arrangement of cytoskeletal structures around the inclusions, degradation of host cell proteins by proteolytic activity, inhibition of apoptosis, fragmentation of the Golgi apparatus and sphingomyelin transport to inclusion, were not observed during W. chondrophila infection [36,37]. These differences may be associated with different tissue tropism and divergent pathogenetic mechanisms.…”
Section: Mode Of Transmission Comments Referencesmentioning
confidence: 94%
See 1 more Smart Citation
“…Expression of these pro-inflammatory mediators occurs through distinct signalling pathways whose stimulation is through interactions of the host cells with specific pathogen associated molecular patterns (PAMPS) [ 7 ]. Comparative studies have demonstrated distinct differences in the membrane structure [ 8 ] and the developmental cycle [ 9 ] of W . chondrophila compared to other pathogenic chlamydial species, which have been suggested to reduce the pathogenicity of the organism.…”
Section: Introductionmentioning
confidence: 99%